2017
DOI: 10.1002/slct.201700547
|View full text |Cite
|
Sign up to set email alerts
|

Correlating Properties in Iron(III) Complexes: A DFT Description of Structure, Redox Potential and Spin Crossover Phenomena

Abstract: Calculations of structure, redox potential and spin transition energies were performed using DFT approximations for a series of [Fe(bztpen)OR] 2 + / + type Fe III /Fe II systems (R=Me, Et, nPr, nBu), which have a temperature dependent spin crossover behavior. These compounds exhibit changes in redox and magnetic properties, related to structural variations quite important for their possible applications among which signal generator materials stand out. Functionals B3LYP, wB97XÀD and TPSS along with PCM solvat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Remarkably, the ionization energies and EAs gave absolute errors starting from 0.9 to 5.9% . The BPW91/6-311 + G­(2d) results approach the outcomings yielded by more sophisticated and expensive methods, of a multireference character, as that proposed by Tzeli et al, being affordable to the study of small iron–carbon clusters.…”
Section: Computational Detailssupporting
confidence: 53%
“…Remarkably, the ionization energies and EAs gave absolute errors starting from 0.9 to 5.9% . The BPW91/6-311 + G­(2d) results approach the outcomings yielded by more sophisticated and expensive methods, of a multireference character, as that proposed by Tzeli et al, being affordable to the study of small iron–carbon clusters.…”
Section: Computational Detailssupporting
confidence: 53%
“…Also it has been proven that, for the electron affinity calculated for bare Fe 4 , BPW91/6-311+G­(2d) performs better than using other functionals, such as B97D, M11L, or PBE0 . Lastly, the BPW91/6-311+G­(2d) method has been shown to approach the results yielded by more sophisticated and expensive methodologies, as that proposed by Tzeli et al Thus, BPW91/6-311+G­(2d) is used in this work, since it has been proven to be affordable to inspect exhaustively the potential energy surface of Fe n CO, n = ≤ 20, needed for its correct characterization (Table ).…”
Section: Methodsmentioning
confidence: 90%
“…At this point, it is worth noting the accuracy of the method. The functional employed has proved to accurately describe C−C bond lengths 46 and non-covalent distances such as those present in the ferrocene system 47 thanks to the inclusion of dispersion corrections. Despite the adequate performance on the geometry, Fokin et al, reported an overestimation of a few kcal mol −1 in the description of rotational barriers.…”
Section: ■ Results and Discussionmentioning
confidence: 99%